Act East Policy of Indian Agriculture - Khatri, D.; Arunachalam, A.; Arunachalam, K. (Indian Journal of Hill Farming, 2018)
In order to enhance agricultural productivity and livelihoods, we all aim to provide new methods of the cropping, practices and technologies. Sustaining agriculture is important to feed the growing requirements of the overwhelming human population. Indian agriculture, owing to high yielding varieties and animal breeds vis-Ã -vis good agricultural practices, has moved its production from shortage to surplus over the years. While India has witnessed green revolution, primarily based on the agricultural development in the north-west plains of the country, today, the government is foresighting second green revolution in the eastern India to harness the potentials of fertile soil and also water resources. Thus, the programme of bringing green revolution to the eastern India is based on the successful recommendation of Task Force in 2009 to assess the existing scenario of water resources development, utilization and management of food grains production in the country.